Students Politeness in Academic Interactions at Higher Education Institutions - Suryani, Indra (Continuous Education: Journal of Science and Research, 2025)
This study aims to describe the forms of politeness in language used by students in academic interactions at STAI Syekh Abdur Rauf Aceh Singkil and the influencing factors. The research method employed is descriptive qualitative with data collection techniques including observation, interviews, and document studies. The results show that students generally apply principles of politeness in direct communication with lecturers and peers, such as using polite address terms, expressions of permission, and structured communication. However, in digital and informal communication, some violations of politeness maxims were found, including the use of brief, informal language and the absence of opening and closing greetings. Students’ politeness is influenced by Islamic values taught on campus, lecturers’ role modeling, and the students’ social environment. These findings suggest the need for the integration of communication ethics education into the curriculum and the development of academic communication guidelines, particularly for digital platforms. Consequently, a culture of polite academic communication can be sustainably nurtured and contribute to a harmonious and productive academic climate.